A detached leaf assay to rapidly screen for resistance of maize to Bipolaris maydis, the causal agent of southern corn leaf blight - Aregbesola, E.; Ortega Beltran, A.; Falade, Titilayo D.O.; Jonathan, G.; Hearne, S.; Bandyopadhyay, Ranajit (Springer, 2020)
Southern corn leaf blight (SCLB), caused by the fungus Bipolaris maydis, is a disease that significantly affects maize productivity across the globe. A detached leaf assay (DLA) was developed to rapidly assess maize resistance to SCLB. Several experiments were conducted to: (i) identify a highly virulent B. maydis isolate; and to determine the most appropriate (ii) phytohormone to maintain viability of maize leaf tissue, (iii) leaf age for the assay, and (iv) inoculum concentration. Once optimized, the DLA was compared with screenhouse and field experiments. Use of DLA required a maximum of 28 days for resistance assessment, in contrast to screenhouse and field tests at a minimum of 33 and 72 days, respectively. DLA positively correlated with screenhouse (r = 0.48, P = 0.08) and field experiments (r = 0.68, P = 0.008). Assessments of diverse B. maydis strains and host genotypes indicated that the DLA could be used to detect both highly virulent SCLB strains and highly resistant maize genotypes. Here we report that DLA is a rapid, reliable technique to screen maize resistance to SCLB. Use of this tool in maize breeding programs can speed up the process of identification of sources of resistance to multiple variants of SCLB.